Gizi Seimbang dan Gangguan Menopause pada Lansia - Rindasari Munir; Indri Widya Sari; Meidyna Rachmani; Nita Alpiyanah; Sindy Nurhalisah (STIKes Ibnu Sina Ajibarang, 2025)
The World Health Organization (WHO) estimates that in 2030 there will be around 1.2 billion women over 50 years old, as many as 30-40% will experience overnutritional status. The purpose of this counseling is to educate the public about the importance of consuming balanced nutrition in the elderly and the handling of menopausal disorders, especially in RW 05 Babakan Village, Ciseeng District. The method carried out is the lecture method with booklet media. The target of this counseling is 67 elderly people. The results of the balanced nutrition knowledge questionnaire were from the pretest as many as 54 people (80.6%) had insufficient knowledge and the posttest as many as 56 people (83.6%) understood balanced nutrition well. Meanwhile, the results of the questionnaire obtained from knowledge about menopausal disorders, namely pretest as many as 51 people (76.1%) had poor knowledge and the results of the posttest 58 people (86.6%) had good knowledge about menopause. The results of the test were T = – 10.874 and p value = 0.000 (<0.05) in the pretest and posttest of balanced nutrition and T – 10.530 and p value = 0.000 (<0.05) in the pretest and posttest of menopause. The conclusion shows that there is an influence of balanced nutrition education and menopausal disorders on the knowledge of elderly mothers.